Autenticidade e reconhecimento no multiculturalismo de Charles Taylor - Nascimento Neto, Antonio Marcelo do (2018)
This dissertation intends to analyze the concept of multiculturalism proposed by the Canadian philosopher Charles Taylor in order to highlight the association of authenticity and recognition presented by the author. Charles Taylor is one of the most influential and recognized contemporary political philosophers. He dedicated part of his work to the reflection of the multicultural reality, creating modern ideals of authenticity and recognition, which has as its mark a notorious balance, as well as providing authentic solutions that attacks the political atomism and the instrumental reason. For this, we analyze the concept of multicuturalism proposed by the author, since it is not explicitly presented in his work, but is disseminated in numerous theoretical formulations.